The Social Responsibility of the Top 100 Romanian Companies. An Analysis of Corporate Websites - Tamara Eugenia Baleanu; Liviu Chelcea; Alin Stancu (Amfiteatru Economic Journal, 2011)
The article identifies the extent to which the most valuable Romanian companies practice corporate social responsibility (CSR) and its beneficiaries. It describes the main areas of action and specific instruments of intervention. The data analysed cover the top 100 Romanian companies, as ranked by Ziarul Financiar. The corporate website of each company was analysed and subsequently codified on multiple variables. The results outline the fact that firms engage in CSR activities to a relatively high extent (49% of the companies). They adopt a vision of corporate social responsibility exclusively centred on the firm and the competitive advantages that derive from CSR activity. The wider community is represented as the primary stakeholder and beneficiary, whilst those stakeholders thought to influence the profit-making goals to a lesser extent are more often than not overlooked. Finally, companies prefer inexpensive intervention instruments and prove weak coordination with others social and political actors.
Keywords: M14; O16; D01; D03; 330; corporate social responsibility; top 100 Romanian companies; corporate social responsibility annual reports; stakeholders